2020
DOI: 10.1016/j.celrep.2020.107543
|View full text |Cite
|
Sign up to set email alerts
|

GDF15 Induces an Aversive Visceral Malaise State that Drives Anorexia and Weight Loss

Abstract: Highlights d Acute GDF15 systemic delivery induces visceral malaise, anorexia, and body weight loss d Chronic GDF15 exposure triggers visceral malaise that does not decline over time d GDF15 conditions food-aversive responses persisting beyond its acute anorectic action d GDF15's visceral malaise and anorectic effects do not require slowed gastric emptying

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 56 publications
4
51
4
Order By: Relevance
“…Together, these and recently published data ( Borner et al, 2020a ; Borner et al, 2020b ) suggest that GDF15 is probably not a natural satiety factor, but exerts a pathophysiological action to cause anorexia. This conclusion is supported by the findings that circulating GDF15 levels do not correlate with meal times in humans, ( Patel et al, 2019 ; Tsai et al, 2015 ) and that GDF15 knock out in mice does not result in significant changes in normal chow intake ( Tsai et al, 2013 ; Tran et al, 2018 ).…”
Section: Resultssupporting
confidence: 59%
“…Together, these and recently published data ( Borner et al, 2020a ; Borner et al, 2020b ) suggest that GDF15 is probably not a natural satiety factor, but exerts a pathophysiological action to cause anorexia. This conclusion is supported by the findings that circulating GDF15 levels do not correlate with meal times in humans, ( Patel et al, 2019 ; Tsai et al, 2015 ) and that GDF15 knock out in mice does not result in significant changes in normal chow intake ( Tsai et al, 2013 ; Tran et al, 2018 ).…”
Section: Resultssupporting
confidence: 59%
“…In fact, GDF-15 was previously observed to be related with inflammatory markers in gastrointestinal cancer patients but not with nutritional parameters, such as body weight loss, anthropometry, and only weakly with low dietary food intake [ 20 ]. On the other hand, the GDF-15 circulating levels were found higher in cancer patients with body weight loss with respect to those with a stable weight [ 10 ], observations that were also recently confirmed in experimental models [ 21 ]. These different results obtained by others, including patients suffering by a miscellaneous of cancer diseases (only male) [ 10 ], or by esophago-gastric cancer [ 20 ] and by our study—focused on lung and gastrointestinal cancer patients—may be in part related to the different populations enrolled and likely to a different stage of cancer disease.…”
Section: Discussionmentioning
confidence: 87%
“…demonstrated that GDF15 showed short-term effects on reducing food intake and longer-term effects on conditioned food aversion [ 83 ]. When rats were administered GDF15 and then exposed to a food substance, they displayed avoidance and disgust toward the food, which lasted well after the anorectic effect of GDF15 had waned; the food aversion remained in the absence of effects on gastric emptying [ 83 ]. These findings suggest that a long-term taste aversion has been established, presumably through involvement of the CTZ as previously discussed.…”
Section: Recent Developments Of Gdf15mentioning
confidence: 99%